Coupling dynamic analysis on T-shaped spatial rigid-flexible combination structure - Weipeng Hu; Xinying Yan; Haitao Zhao; Weiping Wang; Zichen Deng (Advances in Space Research, 2026)

Electric-field-driven ultra-fine fibres (EDF): A sustainable and intelligent platform for future food packaging - Jun-Hu Cheng; Kai Zhang; Zichen Li; Da-Wen Sun (Trends in Food Science & Technology, 2026)

Low-dose fluoride and lead co-exposure alters bone mineral density in youth: A nationally representative cross-sectional study - Chunxiang Li; Zeyuan Niu; Yuhui Du; Lihong Yang; Fan Wu; Xinxin Hu; Xiaohang Meng; Zichen Feng; Shu Niu; Qing Sun; Yan Wang; Xiaoli Fu; et al. (Journal of Trace Elements in Medicine and Biology, 2026)

Integrated assembly the multifunctional composite films using carbon dots greenly synthesized in situ on cellulose nanofibers for active fruit preservation - Lijuan Lan; Jiazhen Cao; Zichen Li; Jun-Hu Cheng (Food Chemistry, 2026)

Plasma assisted electrospinning technology for functional food packaging: Strategies, applications, and prospects - Kai Zhang; Zichen Li; Jun-Hu Cheng (Food Packaging and Shelf Life, 2026)

Mixed ion–electron conductor assembled from sulfonated chitosan and rGO for accelerating Desolvation kinetics and inducing 3D nucleation in Li–S batteries - Jiajun Chen; Jianying Zhang; Yixian Xiao; Yinuo Yu; Yunxiao Ren; Shuoning Zhang; Xinzhao Xia; Wenting Xie; Jiale Liu; Zichen Wang; Lanying Zhang; Wei Hu; et al. (Chemical Engineering Journal, 2026)

Atmospheric Boundary Layer Eco-Environment Shanghuang Observatory: An Integrated Multiscale Research Platform in Southeastern China for Understanding Boundary Layer Processes, Atmospheric Chemistry Feedback, and Extreme Weather–Climate Linkages - Zifa Wang; Xiaole Pan; Yele Sun; Jinyuan Xin; Hang Su; Junji Cao; Jie Li; Ting Yang; Hang Liu; Weijie Yao; Weiqi Xu; Xueshun Chen; et al. (Advances in Atmospheric Sciences, 2026)

A hybrid POD-LSTM framework for efficient vortex-induced vibration prediction in marine risers via multi-fidelity data fusion - Kang Lu; Zheng Zeng; Sheng Zhou; Xiong Xiong; Rongchun Hu; Zichen Deng (Ocean Engineering, 2026)

Piperlongumine Inhibits Malignant Progression of Esophageal Squamous Cells Through the PI3K/AKT Signaling Pathway - Jun Wang; Yueming Chu; Guangbing Hu; Shiqi Liang; Yutong Cui; Ji Zuo; Zichen Luo; Xinrui Chen; Xiaobo Wang; Zhenghang Yu; Zhongyang Zhang; Xianfei Wang (Biochemical Genetics, 2026)

Notch1-dependent hippocampal apoptosis is associated with monocrotaline-induced anxiety-like behavior - Lai Baochang; Li Fan; Wang Fei; Yan Xianchun; Wang Zichen; Han Mengzhuan; Zhang Yiman; Kang Mengyang; Liu Bing; Wang Ying; Ma Qiang; Jia Pu; et al. (Toxicology, 2026)

Modeling hydro-thermal processes in fractured geothermal reservoirs using embedded discrete fracture model (EDFM) and MRST - Tongchao Nan; Tianwei Hu; Zichen Wang; Jiangjiang Zhang; Jina Yin; Yifan Xie; Jichun Wu; Chunhui Lu (Advances in Water Resources, 2025)

Effects of Cardiac Rehabilitation Combined with Enhanced External Counterpulsation on Heart Rate Variability and Autonomic Nervous Function in Chronic Heart Failure - Yiliang Yan; Zichen Han; Bowen Zhou; Kui Li; Jintao Hu; Sigong Yang; Jun Zhang; Xuemin Hu (Cardiovascular Toxicology, 2025)

Washing-inspired self-cleaning bionic solar interfacial evaporator for highly efficient broad-spectrum desalination - Zichen Li; Chunyan Huang; Shuxia Wei; Jun-Hu Cheng; Yuanyuan Ge; Zhili Li (Chemical Engineering Journal, 2025)

Pharmacokinetics of honokiol in Trachinotus ovatus following administration of honokiol monomer and Magnolia officinalis extracts - Weiliang Guo; Danyi Wei; Zichen Zhao; Fengxiao Hu; Dahao Wang; Wei Tang; Yan Wang; Hengwei Deng; Jianlong Li; Dongdong Zhang; Zhihong Zhong; Yongcan Zhou (Aquaculture, 2025)

Electro-oxidation of lincomycin and human pathogenic bacteria using carbon-supported lanthanide derivatives anodes: Accelerating wastewater remediation - Jia Wang; Yihang Hu; Tao Cao; Zichen Duan; Zixuan Zhao; Yifan Sun; Jie Gu; Xiaojuan Wang (Journal of Environmental Management, 2025)

Adsorption mechanism of soy protein amyloid fibrils with different morphological structures at the interface of oil-in-water emulsion - Jingwen Zhao; Baoyue Chang; Yutong Hu; Xiaoshuai Wang; Zichen Cao; Yan Zhang; Zejian Xu; Xiaonan Sui (Food Hydrocolloids, 2025)

The mechanism of pore pressure and adsorption swelling effect on permeability during geological storage of carbon dioxide in coal seams - Zhenbao Li; Zichen Fan; Hu Wang; Shaorui Wang; Chao Li (Fuel, 2025)

Selection and applications of electrocatalysts for electrochemical anodizing oxidation of emerging contaminants in water: A review - Jia Wang; Yihang Hu; Tao Cao; Zichen Duan; Zixuan Zhao; Yifan Sun; Jie Gu; Xiaojuan Wang (Chemical Engineering Journal, 2025)

Enhancing Underwater Video from Consecutive Frames While Preserving Temporal Consistency - Kai Hu; Yuancheng Meng; Zichen Liao; Lei Tang; Xiaoling Ye (Journal of Marine Science and Engineering, 2025)
Current methods for underwater image enhancement primarily focus on single-frame processing. While these approaches achieve impressive results for static images, they often fail to maintain temporal coherence across frames in underwater videos, which leads to temporal artifacts and frame flickering. Furthermore, existing enhancement methods struggle to accurately capture features in underwater scenes. This makes it difficult to handle challenges such as uneven lighting and edge blurring in complex underwater environments. To address these issues, this paper presents a dual-branch underwater video enhancement network. The network synthesizes short-range video sequences by learning and inferring optical flow from individual frames. It effectively enhances temporal consistency across video frames through predicted optical flow information, thereby mitigating temporal instability within frame sequences. In addition, to address the limitations of traditional U-Net models in handling complex multiscale feature fusion, this study proposes a novel underwater feature fusion module. By applying both max pooling and average pooling, this module separately extracts local and global features. It utilizes an attention mechanism to adaptively adjust the weights of different regions in the feature map, thereby effectively enhancing key regions within underwater video frames. Experimental results indicate that when compared with the existing underwater image enhancement baseline method and the consistency enhancement baseline method, the proposed model improves the consistency index by 30% and shows a marginal decrease of only 0.6% in enhancement quality index, demonstrating its superiority in underwater video enhancement tasks.

Quasi-harmonic analysis of fortnightly suspended sediment response to semi-diurnal tidal currents - Zichen Zhu; Bingchen Liang; Bin Chen; Bo Yang; Wanqing Chi; Hao Xu; Zejian Hu (Frontiers in Marine Science, 2024)
Introduction The suspended sediment concentration (SSC) is an important consideration in marine engineering. Sediment movement characteristics can be studied by considering the fortnightly behavior of SSC. However, this consideration currently lacks accurate mathematical representation. Method In this study, a computationally efficient mathematical model capable of providing analytical solutions for predicting SSC based on resuspension, deposition, and advection was developed to further investigate the mathematical interpretation of fortnightly SSC behavior in coastal areas dominated by M2, S2, O1, K1, M4 and MS4 tides. The model decomposed the SSC into 35 quasi-harmonic terms as well as two terms with fortnightly period. Result The model was applied at five observation sites in the Bohai Sea, Yellow Sea and East China Sea, China, and validated to be able to reproduce the fortnightly variation of SSC. The results show that the primary fortnightly SSC term was generated by the combined action of M2 and S2 tidal currents and had a tidal frequency of 1.0159 °/h, which was equal to the difference between the frequencies of the two partial tides. Discussion The resuspension properties only affected the amplitude of the fortnightly SSC term but did not affect the phase. The deposition properties affected both amplitude and phase. The quasi-harmonic analysis indicates that in certain shallow sea areas with strong nonlinear tidal interactions, the amplitude of the M4 tidal elevation can influence the mean SSC, while the amplitude of the MS4 tidal elevation can affect the fortnightly SSC amplitude. As the simplified model is based on certain assumptions, the application conditions of the quasi-harmonic analytical solution include an approximate reciprocating flow pattern, a tidal range significantly smaller than the water depth. Our results provide a mathematical solution for the fortnightly evolution of suspended sediment.

Healable and multi driving mode soft actuator enabled by disulfide-bonded liquid crystal elastomers - Shuoning Zhang; Zichen Wang; Jianying Zhang; Jiale Liu; Chang Sun; Shengyu Qin; Yunxiao Ren; Lanying Zhang; Wei Hu; Huai Yang (Chemical Engineering Journal, 2024)

Dynamic analysis on an asymmetric spatial dumbbell-type model - Weipeng Hu; Bo Tang; Zhengqi Han; Pingwei Deng; Zichen Deng (Advances in Space Research, 2024)

Many-objective evolutionary algorithm based on parallel distance for handling irregular Pareto fronts - Zichen Wei; Hui Wang; Shuai Wang; Zhixia Zhang; Zhihua Cui; Feng Wang; Hu Peng; Jia Zhao (Swarm and Evolutionary Computation, 2024)

Thermo-enviro-economic analysis of a novel landfill gas-fueled CCHP-desalination process combined with a liquefied natural gas cold energy recovery unit - Zichen Xu; Ya-Jian Hu; Yu-Tao He; Tirumala Uday Kumar Nutakki; Asiful H. Seikh; V. Mohanavel; Nehad Ali Shah; Muxing Qin (Journal of Cleaner Production, 2024)

Smartphone-Aided Fluorescence Detection of Cardiac Biomarker Myoglobin by a Ratiometric Fluorescent AuNCs-QDs Nanohybrids Probe with High Sensitivity - Zichen Xu; Hedan Xu; Hongliang Duan; Junjie Li; Xiao Hu; Kaixin Jiang; Guixue Wang; Yuanyuan Zhang (Journal of Fluorescence, 2024)

A 5.5-kb LTR-retrotransposon insertion inside phytochrome B gene (CsPHYB) results in long hypocotyl and early flowering in cucumber (Cucumis sativus L.) - Liangliang Hu; Miaomiao Zhang; Jingjing Shang; Zichen Liu; Yiqun Weng; Hongzhong Yue; Yuhong Li; Peng Chen (Theoretical and Applied Genetics, 2023)

A flight-testing campaign to examine inflight icing characteristics and its effects on the flight performance of an Unmanned-Aerial-Vehicle - Nianhong Han; M.A. Siddique; Zichen Zhang; Linchuan Tian; Haiyang Hu; Hui Hu (Cold Regions Science and Technology, 2023)

Development of novel fermented stinky sea bass and analysis of its taste active compounds, flavor compounds, and quality - Hong Xiao; Jiao Yu; Mengyue Hu; Hongying Liu; Zichen Yuan; Yong Xue; Changhu Xue (Food Chemistry, 2023)

Efficient electrochemical CO2 reduction to CO by metal and nitrogen co-doped carbon catalysts derived from pharmaceutical wastes adsorbed on commercial carbon nanotubes - Yang Gang; Boyang Li; Siyuan Fang; John Pellessier; Lingzhe Fang; Fuping Pan; Zichen Du; Yun Hang Hu; Tao Li; Guofeng Wang; Ying Li (Chemical Engineering Journal, 2023)

Research on an Autonomous Underwater Helicopter with Less Thrusters - Zichen Liu; Jing Zhou; Zhikun Wang; Haifu Zhou; Jie Chen; Xuanshuo Hu; Ying Chen (Journal of Marine Science and Engineering, 2022)
Autonomous underwater helicopter, referred to as AUH, has high maneuverability in the horizontal plane and stable movement in the vertical direction due to its disc shape. Thus, the AUH demonstrates great advantages when working in scenarios that require high accuracy of horizontal movement, fixed height and depth, operation near the seafloor, and so on. In this paper, we propose a new design for an autonomous underwater helicopter with three thrusters in the vertical direction (three-vertical-thrusters), so it is equipped with fewer thrusters while maintaining maneuverability and motion stability. The three-vertical-thruster AUH not only achieves stable attitude control, but also reduces the number of thrusters, enabling the AUH to save space, reduce drag, and decrease power consumption. The three-vertical-thruster structure is designed first and compared with the existing four-vertical-thrusters type to verify its advantages through dynamic analysis and hydrodynamic simulation. The three-vertical-thruster AUH is then modelled, and a compensation method is proposed for its more complex control. The three-vertical-thruster AUH’s controllability and stability are also verified by experiments on the basis of the experimental prototypes.

Modified Mann-Kendall trend test for hydrological time series under the scaling hypothesis and its application - Zichen Hu; Shuguang Liu; Guihui Zhong; Hejuan Lin; Zhengzheng Zhou (Hydrological Sciences Journal, 2020)

Mechanism of Phase Lag Between Current Speed and Suspended Sediment: Combined Effect of Erosion, Deposition, and Advection - Zichen Zhu; Yongzhi Wang; Zejian Hu; Shuhua Bian; Yongqiang Zhang; Congbo Xiong (Journal of Ocean University of China, 2019)

A method for simulating sediment incipient motion varying with time and space in an ocean model (FVCOM): development and validation - Zichen Zhu; Yongzhi Wang; Shuhua Bian; Zejian Hu; Jianqiang Liu; Lejun Liu (Journal of Oceanology and Limnology, 2018)

Sediment suspension and the dynamic mechanism during storms in the Yellow River Delta - Shuhua Bian; Zjian Hu; Jianqiang Liu; Zichen Zhu (Environmental Monitoring and Assessment, 2017)

P2Y6 Receptor-Mediated Microglial Phagocytosis in Radiation-Induced Brain Injury - Yongteng Xu; Weihan Hu; Yimin Liu; Pengfei Xu; Zichen Li; Rong Wu; Xiaolei Shi; Yamei Tang (Molecular Neurobiology, 2016)